Electron tomography of soot for validation of 2D image processing and observation of new structural features. Issue 5 (4th May 2019) - Baldelli, Alberto; Trivanovic, Una; Rogak, Steven N.
Abstract: Transmission electron microscopy of soot aggregates is performed using a tilting-stage with view angles from –60 to +50 degrees. The resulting series of images was used to produce videos and solid models to aid in the visualization of the structure. The images from 31 angles for each aggregate were analyzed using various 2D image processing techniques. It was found that the measurements of primary particle size varied by less than 16% as angles changed. Projected area measurements only varied by 6% as viewing angle changed. These variations are comparable to the errors expected from the image processing. Practically, 2D images are adequate for determining primary particle size and projected area with little noise or bias introduced by random projection angles. In addition, it was found that most of the aggregates contained closed ring structures, implying that during aggregation, a small amount of rotation at contact points occurs. This structural feature is not apparent in 2D images and suggests that tomography may be useful in studying soot formation and aging processes. Copyright © 2019 American Association for Aerosol Research